Avaliação da estabilidade termo-oxidativa do óleo das sementes de quiabo (Abelmoschus esculentus (L.) Moench) - Carvalho, Maria Lucia Braga de (2011)
The evaluation of thermo-oxidative stability is an essential factor for application an of oil in the food industry. In addition, the increase consumption of vegetable oils requires the evaluation of alternative oil sources as feedstock for biodiesel production. This research investigated the thermo-oxidative stability of okra seeds oil (with and without antioxidant) submitted to the Schaal test at 60 °C for 10 days. The oxidation process was evaluated by chemical parameters acidity value (AV), iodine value (IV), peroxide value (PV), extinction value (E) for conjugated dienes, oxidation temperature (OT), induction period (IP) and oxidative induction time (OIT). The results showed that AV and IV values for oil samples with (OQT) and without (OQ) the antioxidant tert-butyl hydroquinone (TBHQ) do not changed after aging in oven. However, OQT samples showed lower PV value, higher IP and OIT values than OQ samples hence high oxidative stability. IP and OIT value for OQT samples remained constant as function of time under heating in oven. Differently OQ samples presented decreasing IP and OIT values and increasing IP value. Regarding to E value it remained constant for OQT samples and increased around 35 % for OQ samples. The increased value of E is an indication that there was formation of conjugated dienes in samples without antioxidant. These data demonstrated the importance of adding antioxidants to protect oil from oxidative degradation. Another parameter used for the purpose of evaluate the oxidative stability of oil has been monitoring the absorption bands in the infrared region, characteristic of oxidation products. Evaluation of infrared spectra of the OQ samples do not show changes in intensity or shifting in the bands that are altered with the decomposition of hydroperoxides formed in heating test. Through thermogravimetric analysis it was determined that the onset temperature decomposition (Tonset) okra oil was higher than for olive, sunflower, canola, soybeans and corn oils. This parameter shows more stability to the okra oil and it was attributed to the fatty acid composition of this oil. Fatty acid composition indicated predominance of linoleic acid (33.5 %) followed by palmitic acid (25.2 %) and oleic acid (19.3 %). It was found that content of linoleic acid, an acid more susceptible to oxidation, is lower when compared with soybean, sunflower and corn oils. It also gives a value of saturated fatty acids (33.4 %) higher than these edibles oils. The results obtained in this study showed that okra seeds oil has good thermal and oxidative stability, and an indication of its use as edible oil and potential source of feedstock for biodiesel.